Reconstructing Culture-Based Tourism through Experiential Cultural Communication: Community Empowerment among the Bali Aga Community in Tenganan Pegringsingan Village, Bali - Ani Purwati; Gita Ruslita (International Journal Of Community Service, 2026)
The transformation of global tourism has shifted the paradigm from mass tourism to experience tourism, emphasizing meaningful experiences as the core value of travel activities. In this context, culture is no longer viewed merely as a tourism attraction but as a communication medium that creates memorable experiences for visitors. Tenganan Pegringsingan Village in Karangasem Regency, Bali, as one of the oldest Bali Aga communities that preserves its traditional social system, customary law (awig-awig), religious rituals, Mekare-kare (Pandan War) tradition, and Gringsing weaving heritage, possesses significant potential for the development of experiential cultural tourism. However, the growth of the tourism industry has also generated challenges, including cultural commodification, diminishing symbolic meanings of traditions, and the predominance of attraction-oriented tourism management over participatory cultural experiences. This community engagement program aims to reconstruct a cultural tourism model through the Experiential Cultural Communication approach, integrating cultural preservation, experiential communication, and community empowerment. The program employed participatory methods, including participatory observation, focus group discussions (FGDs), cultural storytelling training, cultural interpretation assistance, and capacity-building activities for local communities in managing community-based tourism communication. The findings reveal that Bali Aga culture can function as a medium of experiential communication that generates sensory, emotional, intellectual, relational, and transformational experiences for visitors. This approach not only strengthens the cultural identity of the Tenganan Pegringsingan community but also promotes sustainable tourism centered on local participation. The Experiential Cultural Communication model offers a strategic alternative for preserving cultural authenticity while enhancing educational, participatory, and sustainable tourism experiences. Consequently, this reconstruction seeks to position tourists